Psychosocial and demographic correlates of objectively measured physical activity in structured and unstructured after-school recreation sessions - Rosenkranz, Richard R.; Welk, Greg J.; Hastmann, Tanis J.; Dzewaltowski, David A. (My University, 2011)
Most studies of psychosocial and demographic correlates of physical activity (PA) have examined relationships across various types of physical and social environments, rather than within a specific environmental behavior setting. The objective of this study was to investigate correlates of PA in structured and unstructured after-school recreation sessions. This study is cross-sectional. School records, questionnaires, and anthropometry were used to obtain demographic and psychosocial variables. Third and fourth-grade children (n = 230) from seven schools wore Actigraph GT1M accelerometers up to six times per year during after-school programming. Accelerometer data were processed to determine percentage of time in moderate-to-vigorous PA (T scores, reflective of an individual child's PA level relative to group mean, were computed for each session and averaged across sessions). Pearson correlations, point-biserial correlations, and mixed-model analyses were used to determine significant associations with PA for each session type (structured and unstructured). For structured sessions, gender, PA barriers self-efficacy, and PA enjoyment were significantly related to PA. For unstructured sessions, only gender was related to PA. Despite equivalent opportunities to participate in active recreation, boys were more active than girls, and children varied in PA level partly due to psychosocial factors. Our results showed that PA self-efficacy and enjoyment explained variability in structured PA sessions.
Keywords: Children; Physical activity; Exercise; Accelerometer; After school; Determinants